2015
DOI: 10.1021/acscatal.5b01539
|View full text |Cite
|
Sign up to set email alerts
|

How the Same Core Catalytic Machinery Catalyzes 17 Different Reactions: the Serine-Histidine-Aspartate Catalytic Triad of α/β-Hydrolase Fold Enzymes

Abstract: Enzymes within a family often catalyze different reactions. In some cases, this variety stems from different catalytic machinery, but in other cases the machinery is identical; nevertheless, the enzymes catalyze different reactions. In this review, we examine the subset of α/β-hydrolase fold enzymes that contain the serine-histidine-aspartate catalytic triad. In spite of having the same protein fold and the same core catalytic machinery, these enzymes catalyze seventeen different reaction mechanisms. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
240
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(267 citation statements)
references
References 139 publications
(278 reference statements)
13
240
0
Order By: Relevance
“…2A), pNPB forms two hydrogen bonds with NH of Met99 and Tyr32, and its carbonyl carbon is in close proximity to HO of Ser98. The catalytic mechanism of an esterase was reported to be similar to that of an amidase (25). In an amidase, the carbonyl oxygen atom of the substrate initially binds to the active site through the oxyanion hole, which is formed by nitrogen atoms of Tyr32 and Met99.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…2A), pNPB forms two hydrogen bonds with NH of Met99 and Tyr32, and its carbonyl carbon is in close proximity to HO of Ser98. The catalytic mechanism of an esterase was reported to be similar to that of an amidase (25). In an amidase, the carbonyl oxygen atom of the substrate initially binds to the active site through the oxyanion hole, which is formed by nitrogen atoms of Tyr32 and Met99.…”
Section: Resultsmentioning
confidence: 98%
“…ited the highest activity, which may result from the synergistic effects of the two sites (9). Esterase is predicted to be the ancestor of a number of different types of enzymes (25). In the research of evolutionary analysis, Devamani and his coworkers found that the predicted ancestral enzymes of hydroxyl nitrile lyases shared the Ser-His-Asp catalytic triad and that they had a conserved function of hydrolysis of esters (29).…”
Section: Discussionmentioning
confidence: 99%
“…3A). The conversion of 2′ to 1′ relies on the nucleophillic attack of the amino group of Ile1 onto the C7′ position of QA in a regio-and stereo-selective manner, mechanistically similar to the reactions catalyzed by various epoxide hydrolases that belong to the α/β-hydrolase superfamily (25,26). These epoxide hydrolases usually share a Ser-His-Asp triad and catalyze epoxide ring opening by using H 2 O as the nucleophillic agent.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon, collectively known as "promiscuity" [18], presumably allows for an increased fitness of the organism through the evolution of novel catalytic functions. Some prominent examples include the α,β-hydrolase fold [19] that is capable of harnessing 17 different reaction mechanisms [20], P450 monooxygenase-catalyzed cyclization [21], cyclopropanation [14], and γ-humulene synthase that generates 52 different natural products starting from the same polyisoprene substrate [22]. As accelerating promiscuous activities through enzyme engineering constitutes a cornerstone for expanding the catalytic scope of enzymes [15], an enhanced fundamental understanding of the molecular mechanisms underpinning the evolution of the catalytic function is desired.…”
Section: Introductionmentioning
confidence: 99%